What Administrative Law Can Teach the Trademark System - Melissa F. Wasserman (Washington University Law Review, 2016)
In 2014, the Patent and Trademark Office (“Trademark Office” or “Agency”) made national headlines when it cancelled the Washington Redskins’ trademark registration. The Washington Redskins, a National Football League team, is valued at a staggering 2.4 billion dollars, of which a substantial portion of this value is attributed to the Washington Redskins brand. Whether the Trademark Office’s cancellation of the mark REDSKINS will be upheld in federal court will depend intimately upon the application of administrative law to the Agency’s decision. Yet the trademark community has tended to pay little attention to administrative jurisprudence and concomitantly the proper standard of review that should be afforded the Trademark Office’s actions. This Article begins to rectify this deficiency by starting to explore, in a comprehensive manner, the intersection of trademark and administrative law. In doing so, it makes two primary contributions. First, this Article argues that the deference jurisprudence of the US Court of Appeals for the Federal Circuit, which hears the majority of Trademark Office appeals, is wrong as a matter of doctrine. More specifically, it contends that the Federal Circuit fails to afford the Agency sufficient deference with respect to both the Trademark Office’s legal and factual determinations. Second, this Article posits that the proper application of administrative law principles to the Trademark Office’s decisions results in a normatively desirable outcome. Affording the Trademark Office’s decisions more deference, and hence elevating the role of the Agency in trademark disputes, ushers the trademark system into the modern administrative era, which has long recognized the deficiencies associated with judge-driven policy.
Keywords: administrative law; trademark; redskins; PTO